Group awareness in computer-supported collaborative learning environments - Ghadirian, Hajar; Mohd Ayub, Ahmad Fauzi; Silong, Abu Daud; Abu Bakar, Kamariah; Hosseinzadeh, Maryam (Canadian Center of Science and Education, 2016)
It is commonly discussed that a key challenge for online collaboration is to promote group awareness. Although this challenge has gained intensified consideration by scholars, scarce attempt has been devoted into development of a reasonable hypothetical comprehension of what group awareness really is and how it can be studied empirically. This paper discusses the conceptions and the research approaches that underlie research on group awareness in computer-supported collaborative learning circumstances. While reviewing literatures they were classified in three categories (behavioral, knowledge and social awareness) and variations in underlying techniques for visualization of awareness were also provided. It was found that research is dominated by the knowledge awareness, which focus on awareness of self and group members’ level of expertise, skills, prior knowledge of task as well as areas of interest. However, some researchers studied all dimensions of awareness. Findings suggest that the notion of displaying of awareness information has been shifted from implicit to the explicit technique through which users intentionally express their current understanding and feelings or assess self and others and provide necessary information to be visualized. The paper suggests some areas for future empirical investigations and concludes with some theoretical considerations on the nature of group awareness.